Symposium 1: New insulins - Liliana Trifone (Revista de la Sociedad Argentina de Diabetes, 2022)
The first therapeutic use of insulin in 1921 revolutionized the management of Type 1 Diabetes and considerably changed the lives of many patients with other types of diabetes (DM). Many advances have taken place in the field of insulin therapy in the last century. , to achieve optimal glycemic control and reduce complications from DM. There are still great challenges such as increasing treatment flexibility, reducing iatrogenic hypoglycemia and optimizing the patient's quality of life. The problems with the action profile and extreme variability of the first insulins have been resolved with progressive modifications in their formulation.